Improving Employee Achievement with Training and Compensation Empirical Study in PT. Sesawi Prima Mandiri - Malalantang, Drevy (HM Publisher, 2023)
This research aims to determine the effect of training and compensation on increasing employee work performance at PT. Sesawi Prima Mandiri. This type of research is quantitative. The data source used in this research is a questionnaire by employee respondents at PT Sesawi Prima Mandiri with a sample size of 50 respondents. This research uses multiple regression analysis. Based on the research results, it is known that training and compensation partially and simultaneously have a significant positive effect on employees at PT. Sesawi Prima Mandiri. The analysis results through calculating the correlation coefficient (R) show a solid positive relationship between training and compensation factors and employee work performance variables (Y). The results of the analysis through calculating the coefficient of determination (R2) show that training and compensation factors have a reasonably significant contribution or contribution to the variation (up and down) of employee work performance (Y), in addition to the variation explained by other factors.